Dataset of turnout rates for European Parliament and municipal elections 2009-2018 - Hutcheson, Derek S. (Malmö University, 2020)
The inventory catalogues available sources of official information on turnout and electoral registration amongst mobile EU citizens for the two most European Parliament elections, prior to 1 January 2019 (2009 and 2014, except for Croatia in 2013) and the most recent municipal elections to which Directive 94/80/EC applied, prior to 1 January 2019. This inventory was funded by the European Union’s Rights, Equality and Citizenship Programme (2014-2020). The content of this inventory represents the views of the authors only and is their sole responsibility. The European Commission does not accept any responsibility for use that may be made of the information it contains.

Database based on primary sources.

The dataset was originally published in DiVA and moved to SND in 2024.
Dataset of turnout rates for European Parliament and municipal elections 2009-2018
Keywords: electoral registration; electoral registration; municipal elections; municipal elections; European Parliament elections; European Parliament elections; electoral turnout; electoral turnout; Political Science; Statsvetenskap